Perbedaan Penerapan Model Pembelajaran TGT-Problem Posing dan Jigsaw Terhadap Minat dan Hasil Belajar - Yosi Nur Kholiso (Jurnal Pendidikan Informatika (EDUMATIC), 2017)
Learning processes that use less attractive methods will have an impact on results and activeness, as well as student interest in learning. Therefore, the need for models and methods that can foster interest and student learning outcomes, namely the TGT model combined with problem posing. This study aims to determine the effect of the TGT-Problem Posing model on student learning outcomes and learning interest. This study uses a pretest-posttest control group design. The population in this study is the third semester informatics education study students consisting of 2 classes. Samples used in class A research as experimental group and class B as control group using saturated sample techniques. The independent variables in this study are the TGT-Problem Posing and jigsaw models, and the dependent variable is the learning outcomes and student learning interest. The results showed that the TGT-Problem Posing learning model in the class in the experimental class had an average value of learning outcomes higher compared to the control class 87.6 78.7. There are differences in interests and learning outcomes between the TGT-problem posing learning model and the jigsaw model.